Pics or it didn't happen the influence of self-monitoring and impression management strategies on millennial yuppies' perceived success of self-presentation Allison Ilagan Laxamana, Jaslyn Samantha Regal Nicolas ; Jonalou S. Labor, adviser. - Laxamana, Allison Ilaga 1995-; Nicolas, Jaslyn Samantha Regal (2018)
This thesis examines how self-monitoring and impression management strategies play a role in the perceived success of self-presentation of Filipino millennial yuppies on Facebook. Millennial yuppies are internet-savvy individuals who are able to use Facebook to build a desirable self-presentation. Millennial yuppies are also going through the transition from college to the workforce. The study is grounded by Goffman (1959)'s work on self-presentation, theory on self-monitoring, and impression management strategies. The researchers conducted an online survey and categorized the yuppies into typologies of self-monitoring and use of impression management strategies. Semi-structured in-depth interviews were also conducted to further understand these typologies. It is indicated that perceived self-presentation success scores differed minimally across typologies. Furthermore, the qualitative data reflected varied notions of a successful Facebook post among the informants. The respondents generally displayed behaviors of high self-monitors and used impression management to a high extent. Self-monitoring was moderately and positively associated with use of impression management strategies. Results further showed that millennial yuppies put a premium on the way they present themselves on Facebook and have a variety of strategies and considerations for presenting their best selves."